Cytotoxic Activity of Ethanol Extract in Namnam Leaves (cynometra cauliflora l.) to Hela Cell - Syarah Anliza; Nurmeily Rachmawati (Department of Chemistry Faculty of Science and Technology Walisongo, 2021)
Cervical cancer is one of the most prominent death cases after breast cancer for a woman in Indonesia. Several treatments can be conducted to cure cancer such as chemotherapy, radiotherapy, tumor surgery, and others. In addition, people can consume some medicines or natural substances that can suppress cancer growth. The natural substances contain active compounds that have the potential as anticancer. One of the natural substances used in this research is the Namnam leaves which grow in Southeast Asia. The purpose of this research was to determine the potential compounds in Namnam leaves extract by cytotoxic activity testing by using HeLa cells. The active compound in the Namnam leaves extract was obtained by using the maceration method with ethanol for 3x24 hours. The extract was then tested by BSLT method and proliferation by using HeLa cancer cells (ATCC CCL-2). The toxicity results showed that LC50 value was 125,89 μg/mL. This result indicated that the extract belongs to the moderate toxic category and has potential as an anticancer agent. Proliferation test in inhibiting of HeLa cancer cells used Microculture Tetrazolium Technique (MTT) method. The result showed that the extract with a concentration of 25 μg/mL could inhibit the proliferation of HeLa cancer cells by 57,51%.